Answer:
y = -4x - 6
Step-by-step explanation:
y = -4x + b
6 = -4(-3) + b
6 = 12 + b
-6 = b
Answer:
r = 18
Step-by-step explanation:
r -8 = 10
r -8 + 8 = 10 + 8
r = 18
Answer:
-7
Step-by-step explanation:
Lets assume the number Peggy is thinking of be "x".
Now as given, when twice the number is added to three times one more than the number. We can write it as
∴
--- Equation 1
Again, it is given that Peggy gets the same result as when she multiplies four times one less than the number.
∴
-- equation 2
Next, we can equate both the equation 1 and 2 as it is given that result is same.
![2x+3(x+1)= 4(x-1)](https://tex.z-dn.net/?f=2x%2B3%28x%2B1%29%3D%204%28x-1%29)
Let´s distribute 3 into
and 4 into ![(x-1)](https://tex.z-dn.net/?f=%28x-1%29)
⇒ ![2x+3x+3=4x-4](https://tex.z-dn.net/?f=2x%2B3x%2B3%3D4x-4)
⇒ ![5x+3=4x-4](https://tex.z-dn.net/?f=5x%2B3%3D4x-4)
Subtract both side by 4x and 3
∴ ![x=-7](https://tex.z-dn.net/?f=x%3D-7)
∴ Peggy was thinking of -7
It will be a negative.
for an example: -20 for x would mqke 2x + 1 into -39 and 8x + 5 into -155. that's 116 apart, so maybe -2(8) + 5 = -11
-2(2) + 1 = -3
but that's only 8 apart, so it'd be higher.
-4(2) + 1 = -7
-4(8) + 5 = -27
BOOM
Tadaaaa,
You probably thought positive, but sometimes it's negative, you know what I mean?
Answer:
dont listen to this kid its $30.00 on APEX
Step-by-step explanation: